Temperature-dependent cellulose nanofiber oil-water separation membrane and preparation method thereof
By grafting the sulfonate betaine fragments onto cellulose nanofibers and blending them with PVA, a temperature-dependent cellulose nanofiber oil-water separation membrane was prepared, which solved the problem of insufficient water flux at high temperatures in the existing membrane materials, and achieved efficient oil-water separation and long-term stability.
Patent Information
- Application Number
- CN202411754093.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing oil-water separation membrane materials have insufficient water flux in high temperature environments and are difficult to achieve temperature response performance, which affects separation efficiency and stability.
The temperature-dependent cellulose nanofiber oil-water separation membrane was prepared by grafting the sulfonate betaine fragment (SB) under alkaline conditions to form modified cellulose nanofibers and physically blended with polyvinyl alcohol (PVA).
It achieves that the water flux in high-temperature environments is significantly higher than that in low-temperature environments, imparting temperature response characteristics to the membrane material, improving separation performance and long-term cycle stability, and controlling flux.
Smart Images

Figure CN119565405A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cellulose-based oil-water separation membrane material, in particular to a temperature-dependent cellulose nanofiber oil-water separation membrane material and a preparation method thereof, belonging to the technical field of new materials. Background Art
[0002] During the process of oil exploration and transportation, frequent oil spills often have catastrophic effects on marine ecosystems. The materials used for oil-water separation membranes on the market are mainly synthetic polymers such as polysulfone, polyether, polyacrylonitrile, and polyvinylidene fluoride. The above polymers usually have poor hydrophilicity, low separation efficiency, and are difficult to biodegrade. In contrast, biomass-based oil-water separation membrane materials have received great social attention in recent years due to their advantages such as good hydrophilic effect, easy access to raw materials, low preparation cost, green environmental protection, and excellent oil-water separation efficiency. Among them, cellulose is the most abundant natural biomass polymer in nature. The fiber membrane material prepared by cellulose, especially cellulose nanofibers, has the advantages of large specific surface area, high porosity, and good separation efficiency, and is widely used in oil-water separation membrane materials.
[0003] Flux is an important indicator to measure the separation performance of oil-water separation membrane materials, and pore volume is a key factor affecting the flux of membrane materials. Generally, increasing the pore volume of membrane materials can increase their flux, but at the same time it will reduce their mechanical properties. Regulating the flux of membrane materials according to external stimulus conditions such as pH, gas, and temperature provides a new strategy for effectively treating oily wastewater. pH-regulated oil-water separation membrane materials can efficiently treat surfactant-stabilized oil-water mixed emulsions, but the solutions separated by most membrane materials will also be acidic or alkaline, which will cause secondary pollution to a certain extent. Gas-regulated wettability regulation of membrane materials will not cause a large accumulation of chemical reactions on their surface, but it requires additional gas consumption, and the separation effect of some emulsified oil-water mixtures is not good. In oil-water separation, hydrophilic modified cellulose membrane materials can give them higher water permeation flux and separation efficiency. For example, cellulose acetate (CA) is used as the basic material for membrane manufacturing, and graphene oxide (GO) is electrohydrodynamically atomized to enhance its hydrophilicity. The optimized GO-based CA membrane exhibits higher water permeation flux and separation efficiency than CA membrane (see Fabrication and characterization of superhydrophilic graphene-based electrospun membranes for efficient oil-water separation, Journal of Water Process Engineering, 2023, 54: 104066). In contrast, the use of temperature-responsive hydrophilic thermosensitive compounds grafted on the surface of the membrane material can not only increase the water permeation flux and separation efficiency of the membrane material, but also realize the temperature-controlled switching of the material wettability, which is a hot research direction for oil-water separation membrane materials. Compared with the lower critical solution temperature response (LCST) temperature-controlled membrane material, the upper critical solution temperature response (UCST) regulation is more operational and practical. However, there are currently few studies on UCST-responsive membrane materials, and few reports. Studies have shown that the homopolymer (PSPE) synthesized by aqueous solution free radical polymerization of sulfobetaine monomer (SPE) has UCST response. The polymer exhibits more hydrophilic characteristics at high temperature than at low temperature (see The synthesis of a UCST-type zwitterionic polymer for the efficient recycling of cellulase at room temperature, Green Chemistry, 2021, 23, 2738).Lignin itself does not have temperature responsiveness, but by grafting sulfobetaine fragments (SB) onto lignin, it is given temperature responsiveness (see Synthesis of temperature and pH responsive lignin-grafted sulfobetaine for efficient recycling cellulase, Bioresource Technology, 2023, 369: 128357). In summary, the use of SB grafting to modify cellulose nanofibers is expected to give them UCST responsiveness and hydrophilicity. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a temperature-dependent cellulose nanofiber oil-water separation membrane and a preparation method thereof, which utilizes the temperature response performance of the membrane material to achieve a significantly higher water flux in a high temperature environment than in a low temperature environment, thereby giving the nanofiber membrane material the characteristic of temperature response.
[0005] In order to achieve the above technical problems, the present invention first discloses a temperature-dependent cellulose nanofiber oil-water separation membrane, wherein the oil-water separation membrane is obtained by mixing modified cellulose nanofibers and polyvinyl alcohol and then forming a membrane through a casting method, wherein the modified cellulose nanofibers are obtained by grafting a sulfobetaine fragment (SB) represented by formula (I) on the hydroxyl site of the cellulose nanofibers under alkaline conditions.
[0006]
[0007] Furthermore, the mass ratio of the modified cellulose nanofibers to polyvinyl alcohol is 3 to 19:1.
[0008] Furthermore, the mass ratio of the sulfobetaine fragment represented by formula (I) to the cellulose nanofibers is 1 to 60:1.
[0009] The present invention also discloses a method for preparing the temperature-dependent cellulose nanofiber oil-water separation membrane as described above.
[0010] (1) grafting the sulfobetaine fragment represented by formula (I) onto cellulose nanofibers at 40-60° C. and pH=11-12 for 0.5-6 h to obtain modified cellulose nanofibers, wherein the pH can be adjusted by using a 1 mol / L sodium hydroxide alkaline solution;
[0011] (2) The modified cellulose nanofibers and polyvinyl alcohol solution are physically mixed at 20-30°C for 0.5-2h to obtain a suspension, and the suspension is then cast into a membrane to prepare a temperature-dependent cellulose nanofiber oil-water separation membrane.
[0012] Furthermore, the drying temperature during casting and forming the film in step (2) is 30 to 40° C., and the drying and film-forming time is 6 to 9 hours.
[0013] Furthermore, the sulfobetaine fragment represented by formula (I) is prepared by the following steps:
[0014] (1) Add a certain amount of N,N-dimethylethanolamine and sodium 3-bromopropane sulfonate to N,N-dimethylacetamide, mix well, heat the system to 60-80°C, and stir at constant temperature for 10-16 hours. After the reaction is completed, vacuum filtration is performed to obtain crude HSB (chlorine in the SB molecule shown in formula (I) is replaced by hydroxyl group), and then beating with tetrahydrofuran to obtain refined HSB. The amount of tetrahydrofuran used in this step can meet the beating requirements. Generally, the mass volume ratio of crude HSB to tetrahydrofuran is 0.5-1.5 g:3 mL;
[0015] (2) adding the purified HSB obtained in step (1) to thionyl chloride, stirring and reacting at a constant temperature of -10 to 10°C for 4 to 8 hours, and after the reaction is completed, distilling under reduced pressure to obtain a crude product, and then beating with trifluoroethanol, and then adding tetrahydrofuran to precipitate the target product, and finally freeze-drying to obtain a purified sulfobetaine fragment.
[0016] Furthermore, in step (1), the mass volume ratio of sodium 3-bromopropane sulfonate and N,N-dimethylethanolamine is 0.5-1.5 g:2 mL.
[0017] Furthermore, in step (1), the mass volume ratio of sodium 3-bromopropane sulfonate and N,N-dimethylacetamide is 0.5-1.5 g:20 mL.
[0018] Furthermore, in step (2), the mass volume ratio of HSB to thionyl chloride is 0.5-1.5 g:9 mL.
[0019] Furthermore, in step (2), the mass volume ratio of the refined HSB to trifluoroethanol is 0.5-1.5 g:3 mL, and the mass volume ratio of the refined HSB to tetrahydrofuran is 0.5-1.5 g:3 mL.
[0020] The present invention gives cellulose-based membrane materials UCST response for the first time, and uses the temperature response performance of the membrane material to achieve a water flux in a high temperature environment that is significantly higher than that in a low temperature environment, giving the nanofiber membrane material the characteristic of temperature response, thereby achieving excellent separation performance and also giving the membrane material long-term cycle stability. In addition, the present invention makes the flux controllable by controlling the feed amount of the intermediate SB. When the mass proportion of PVA in CNFS-3 / PVA in the composite membrane is 10%, the fracture strength of the composite membrane can reach 61.42MPa, and the elongation at break can reach 10.9%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a diagram showing the test results of the oil-water mixture separation performance of the oil-water separation membrane of the present invention;
[0022] Figure 2 This is a diagram showing the test results of the oil-water emulsion separation performance of the oil-water separation membrane of the present invention. DETAILED DESCRIPTION
[0023] The present invention is further explained below in conjunction with the examples. The following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0024] The reagents used in the following examples are all commercially available. The oil-water separation flux is measured using a microfilter.
[0025] Preparation of sulfobetaine fragment (SB) represented by formula (I):
[0026]
[0027] (1) At room temperature, 44 mL of N,N-dimethylethanolamine and 24 g of sodium 3-bromopropane sulfonate were added to 480 mL of N,N-dimethylacetamide and mixed evenly. The system was then heated to 70°C and stirred at constant temperature for 12 hours. After the reaction was completed, the crude product of the intermediate product HSB was obtained by vacuum filtration, and finally refined HSB was obtained by beating with tetrahydrofuran.
[0028] (2) At room temperature, 15 g of the purified HSB obtained in step (1) was added to 126 mL of thionyl chloride, and the mixture was stirred at a constant temperature of 5° C. for 5.5 h. After the reaction was completed, a crude product of sulfobetaine fragment (SB) was obtained by vacuum distillation, and the mixture was further slurried with 40 mL of trifluoroethanol. Then, 40 mL of tetrahydrofuran was added to precipitate the target product. Finally, the purified sulfobetaine fragment (SB) was obtained by freeze drying.
[0029] Preparation of temperature-dependent cellulose nanofiber oil-water separation membrane:
[0030] (1) Cellulose nanofibers and sulfobetaine fragment (SB) monomers were used to graft SB fragments onto the hydroxyl sites of cellulose nanofibers at 60°C and alkaline conditions (pH = 11-12 with 20wt% sodium hydroxide solution) to synthesize CNFS-x (x = natural number, representing different batches, corresponding to different grafting degrees of SB and CNF). The grafting reaction was carried out for 5 hours. After the reaction was completed, the fibers were washed with distilled water until the pH value reached about 7.
[0031] (2) Preparation of PVA (polyvinyl alcohol) solution: Add 5 g of PVA to 95 mL of distilled water at room temperature, place in a 70°C constant temperature water bath for 40 min, then gradually heat to 90°C and stir for 1 h to obtain a PVA solution;
[0032] A certain amount of CNFS-x was put into a beaker and ultrasonically dispersed for 30 minutes for later use. A certain amount of prepared PVA solution was then put into a beaker to obtain a CNFS-x / PVA mixed solution. The mixed solution was uniformly stirred on a magnetic stirrer for 2 hours. Finally, a composite membrane was prepared by a casting film method, which was poured into a film casting mold and dried at 40°C for 9 hours. After drying, the CNFS-x / PVA composite film was peeled off to obtain the temperature-dependent cellulose nanofiber oil-water separation membrane of the present invention.
[0033] Comparative Example 1
[0034] Preparation of CNF / PVA composite films
[0035] The specific experimental steps of CNF / PVA composite film are as follows: 5g PVA and 95g deionized water are mixed, placed in a 70℃ constant temperature water bath for 40min, then gradually heated to 90℃ and stirred for 1h to obtain a PVA solution. 9mL CNF is placed in a beaker, ultrasonically dispersed for 30min, and then 1mL PVA solution is placed in a beaker to obtain a CNF / PVA mixed solution, which is stirred at a constant speed on a magnetic stirrer for 2h. Finally, a composite film is prepared by casting, poured into a film casting mold, and dried at 40℃ for 9h to obtain a CNF / PVA composite film.
[0036] Oil-water mixture separation test 1: 10 mL of oil phase (toluene, petroleum ether, n-heptane and n-hexane) and 10 mL of water phase were mixed and poured into the separator. During the oil-water separation process, the effective contact area between the CNF / PVA composite film and the oil-water mixture was 7.06 cm 2 The oil-water separation performance was tested at 25°C. The oil-water mixture was separated under gravity without any other external force. The results are shown in Table 1.
[0037] Oil-water mixture separation test 2: 10 mL of oil phase (toluene, petroleum ether, n-heptane and n-hexane) and 10 mL of water phase were mixed and poured into the separator. During the oil-water separation process, the effective contact area between the CNF / PVA composite film and the oil-water mixture was 7.06 cm 2 The oil-water separation performance was tested at 35°C. The oil-water mixture was separated under gravity without any other external force. The results are shown in Table 1.
[0038] Oil-water emulsion separation test: Four types of emulsions were prepared with toluene, petroleum ether, n-heptane and n-hexane as the oil phase, water as the continuous phase and Tween 80 as the surfactant. The four emulsions were toluene / water, petroleum ether / water, n-heptane / water and n-hexane / water. The effective contact area between CNF / PVA composite film and oil-water emulsion was 7.06 cm 2 The emulsion separation performance was tested at 25°C. The oil-water emulsion was separated under pressure, with a pressure of ΔP = 0.095 bar. The results are shown in Table 1.
[0039] Example 1
[0040] The specific experimental steps of CNFS-1 / PVA (modified by CNF: 0.1g, SB: 0.36g, mass ratio 1: 3.6) composite film are as follows: 5g PVA and 95g deionized water were mixed, placed in a 70℃ constant temperature water bath for 40min, then gradually heated to 90℃, stirred for 1h, and PVA solution was obtained. 9mL CNFS-1 (about 0.09g) was taken in a beaker, ultrasonically dispersed for 30min for use, and then 1mL PVA solution (containing about 0.01g PVA) was taken in a beaker to obtain a CNFS-1 / PVA mixed solution, and the mixed solution was stirred at a uniform speed on a magnetic stirrer for 2h. Finally, a composite film was prepared by a casting film method, poured into a film casting mold, and dried at 40℃ for 9h to obtain a composite film.
[0041] Oil-water mixture separation test 1: 10 mL of oil phase (toluene, petroleum ether, n-heptane and n-hexane) and 10 mL of water phase were mixed and poured into the separator. During the oil-water separation process, the effective contact area between the CNFS-1 / PVA composite film and the oil-water mixture was 7.06 cm 2 The oil-water separation performance was tested at 25°C. The oil-water mixture was separated under gravity without any other external force. The results are shown in Table 1.
[0042] Oil-water mixture separation test 2: 10 mL of oil phase (toluene, petroleum ether, n-heptane and n-hexane) and 10 mL of water phase were mixed and poured into the separator. During the oil-water separation process, the effective contact area between the CNFS-1 / PVA composite film and the oil-water mixture was 7.06 cm 2 The oil-water separation performance was tested at 35°C. The oil-water mixture separation was carried out under the action of gravity without any other external force. The results are shown in Table 1.
[0043] Oil-water emulsion separation test: Four types of emulsions were prepared with toluene, petroleum ether, n-heptane and n-hexane as the oil phase, water as the continuous phase and Tween 80 as the surfactant. The four emulsions were toluene / water, petroleum ether / water, n-heptane / water and n-hexane / water. The effective contact area between CNFS-1 / PVA composite film and oil-water emulsion was 7.06 cm 2 The emulsion separation performance was tested at 25°C. The oil-water emulsion was separated under pressure, with a pressure of ΔP = 0.095 bar. The results are shown in Table 1.
[0044] Example 2
[0045] The specific experimental steps of CNFS-2 / PVA (modified by CNF: 0.1g, SB: 2.84g, mass ratio 1: 28.4)) composite film are as follows: 5g PVA and 95g deionized water are mixed, placed in a 70℃ constant temperature water bath for 40min, then gradually heated to 90℃, stirred for 1h, and a PVA solution is obtained. 9mL CNFS-2 (about 0.09g) is taken in a beaker, ultrasonically dispersed for 30min for use, and then 1mL PVA solution (containing about 0.01g PVA) is taken in a beaker to obtain a CNFS-2 / PVA mixed solution, and the mixed solution is stirred at a uniform speed on a magnetic stirrer for 2h. Finally, a composite film is prepared by a casting film method, poured into a film casting mold, and dried at 40℃ for 9h to obtain a composite film.
[0046] Oil-water mixture separation test: 10 mL of oil phase (toluene, petroleum ether, n-heptane and n-hexane) and 10 mL of water phase were mixed and poured into the separator. During the oil-water separation process, the effective contact area between the CNFS-2 / PVA composite film and the oil-water mixture was 7.06 cm 2 The oil-water separation performance was tested at 35°C. The oil-water mixture was separated under gravity without any other external force. The results are shown in Table 1.
[0047] Oil-water emulsion separation test: Four types of emulsions were prepared with toluene, petroleum ether, n-heptane and n-hexane as the oil phase, water as the continuous phase and Tween 80 as the surfactant. The four different emulsions are toluene / water, petroleum ether / water, n-heptane / water and n-hexane / water. The effective contact area between CNFS-2 / PVA composite film and oil-water emulsion is 7.06 cm 2 The emulsion separation performance was tested at 25°C. The oil-water emulsion was separated under pressure, with a pressure of ΔP = 0.095 bar. The results are shown in Table 1.
[0048] Example 3
[0049] The specific experimental steps of CNFS-3 / PVA (modified by CNF: 0.1g, SB: 5.68g, mass ratio 1: 56.8) composite film are as follows: 5g PVA and 95g deionized water are mixed, placed in a 70℃ constant temperature water bath for 40min, then gradually heated to 90℃, stirred for 1h, and a PVA solution is obtained. 9mL CNFS-3 (about 0.09g) is taken in a beaker, ultrasonically dispersed for 30min for use, and then 1mL PVA solution (containing about 0.01g PVA) is taken in a beaker to obtain a CNFS-3 / PVA mixed solution, and the mixed solution is stirred at a uniform speed on a magnetic stirrer for 2h. Finally, a composite film is prepared by a casting film method, poured into a film casting mold, and dried at 40℃ for 9h to obtain a composite film.
[0050] Oil-water mixture separation test: 10 mL of oil phase (toluene, petroleum ether, n-heptane and n-hexane) and 10 mL of water phase were mixed and poured into the separator. During the oil-water separation process, the effective contact area between the CNFS-3 / PVA composite film and the oil-water mixture was 7.06 cm 2 The oil-water separation performance was tested at 35°C. The oil-water mixture was separated under gravity without any other external force. The results are shown in Table 1.
[0051] Oil-water emulsion separation test: Four types of emulsions were prepared with toluene, petroleum ether, n-heptane and n-hexane as the oil phase, water as the continuous phase and Tween 80 as the surfactant. The four different emulsions are toluene / water, petroleum ether / water, n-heptane / water and n-hexane / water. The effective contact area between CNFS-3 / PVA composite film and oil-water emulsion is 7.06 cm 2 The emulsion separation performance was tested at 25°C. The oil-water emulsion was separated under pressure, with a pressure of ΔP = 0.095 bar. The results are shown in Table 1.
[0052] Table 1 Oil-water separation performance of different CNFS-x / PVA composite films
[0053]
[0054] As can be seen from Table 1, the higher the SB fragment grafted onto the cellulose nanofibers (i.e., the higher the grafting rate of SB), the better the separation performance of the oil-water mixture and the oil-water emulsion. This may be attributed to the fact that with the increase of the grafting degree, the hydrophilicity of the composite film is further enhanced, which is specifically reflected in the fluxes of CNFS-3 / PVA being 1456 and 1160 L m-1, respectively. -2 h -1 The separation efficiencies were 98.8% and 96.5%, respectively; while the flux of unmodified CNF / PVA under the same conditions was only 25 L m -2 h -1and 86L m -2 h -1 As can be seen from Example 1, the flux (water) of the composite film at high temperature (35°C) is significantly higher than the flux at room temperature (25°C). In summary, the above-mentioned cellulose-based oil-water separation membrane material can achieve temperature-dependent flux regulation.
[0055] The above examples are only specific embodiments of the present invention. The present invention is not limited to the above examples, and many variations are possible. All variations that can be directly derived or associated with the contents disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A temperature-dependent cellulose nanofiber oil-water separation membrane, characterized in that: The oil-water separation membrane is obtained by mixing modified cellulose nanofibers and polyvinyl alcohol and then forming a membrane through a casting method. The modified cellulose nanofibers are obtained by grafting a sulfobetaine fragment represented by formula (I) on the hydroxyl site of the cellulose nanofibers under alkaline conditions.
2. The temperature-dependent cellulose nanofiber oil-water separation membrane according to claim 1, characterized in that: The mass ratio of the modified cellulose nanofibers to polyvinyl alcohol is 3 to 19:
1.
3. The temperature-dependent cellulose nanofiber oil-water separation membrane according to claim 1, characterized in that: The mass ratio of the sulfobetaine fragment represented by formula (I) to the cellulose nanofibers is 1 to 60:
1.
4. A method for preparing a temperature-dependent cellulose nanofiber oil-water separation membrane according to any one of claims 1 to 3, characterized in that: (1) grafting the sulfobetaine fragment represented by formula (I) onto cellulose nanofibers at 40-60° C. and pH=11-12 for 0.5-6 h to obtain modified cellulose nanofibers; (2) The modified cellulose nanofibers and polyvinyl alcohol solution are physically mixed at 20-30°C for 0.5-2h to obtain a suspension, and the suspension is then cast into a membrane to prepare a temperature-dependent cellulose nanofiber oil-water separation membrane.
5. The method for preparing the temperature-dependent cellulose nanofiber oil-water separation membrane according to claim 4, characterized in that: The drying temperature during casting and forming the film in step (2) is 30 to 40° C., and the drying and forming film time is 6 to 9 hours.
6. The method for preparing the temperature-dependent cellulose nanofiber oil-water separation membrane according to claim 4, characterized in that: The sulfobetaine fragment represented by formula (I) is prepared by the following steps: (1) Add a certain amount of N,N-dimethylethanolamine and sodium 3-bromopropane sulfonate to N,N-dimethylacetamide, mix well, heat the system to 60-80° C., stir and react at constant temperature for 10-16 hours, and after the reaction is completed, vacuum filter to obtain crude HSB, and then beat with tetrahydrofuran to obtain refined HSB; (2) adding the purified HSB obtained in step (1) to thionyl chloride, stirring and reacting at a constant temperature of -10 to 10°C for 4 to 8 hours, and after the reaction is completed, distilling under reduced pressure to obtain a crude product, and then beating with trifluoroethanol, and then adding tetrahydrofuran to precipitate the target product, and finally freeze-drying to obtain a purified sulfobetaine fragment.
7. The method for preparing the temperature-dependent cellulose nanofiber oil-water separation membrane according to claim 6, characterized in that: In step (1), the mass volume ratio of sodium 3-bromopropane sulfonate and N,N-dimethylethanolamine is 0.5-1.5 g:2 mL.
8. The method for preparing the temperature-dependent cellulose nanofiber oil-water separation membrane according to claim 6, characterized in that: In step (1), the mass volume ratio of sodium 3-bromopropane sulfonate and N,N-dimethylacetamide is 0.5-1.5 g:20 mL.
9. The method for preparing the temperature-dependent cellulose nanofiber oil-water separation membrane according to claim 6, characterized in that: In step (2), the mass volume ratio of HSB to thionyl chloride is 0.5-1.5 g:9 mL.
10. The method for preparing the temperature-dependent cellulose nanofiber oil-water separation membrane according to claim 6, characterized in that: In step (2), the mass volume ratio of the refined HSB to trifluoroethanol is 0.5-1.5 g:3 mL, and the mass volume ratio of the refined HSB to tetrahydrofuran is 0.5-1.5 g:3 mL.
Citation Information
Patent Citations
Temperature response hollow fiber separation membrane
CN101985086A
Preparation method and application of temperature-sensitive switchable emulsion type oil-water separation membrane
CN114832647A
Aqueous phase separation method
US20180318775A1